Characteristics of Trunk Acceleration and Angular Velocity in Turning Movement in Post-Stroke Patients with High Risk of Falling - Daiki Naito; Keita Honda; Yusuke Sekiguchi; Shin-Ichi Izumi; Satoru Ebihara (Sensors)
Although falls commonly occur in post-stroke patients during turning, the characteristics of trunk movement during turning in individuals at a high risk of falling remain unclear. The aim of this study was to clarify the characteristics of trunk translational and rotational movements during turning in post-stroke patients with a high risk of falling. Trunk acceleration and angular velocity were measured using the inertial measurement unit of an iPhone in the timed up and go test and compared among 13 post-stroke patients with a high risk of falling (age: 69.38 ± 12.44 years, Berg Balance Scale (BBS) < 45), 18 post-stroke patients with a low risk of falling (age: 71.22 ± 8.50 years, BBS <semantics>≥</semantics> 45), and 10 age-matched healthy controls (age: 65.90 ± 11.57). We examined the differences in trunk movement during turning between groups and the relationships between the BBS score and trunk movement. The high-risk group exhibited the longest completion time (χ2 = 31.21, p < 0.001) and the lowest maximum of trunk angular velocity along the vertical axis among groups (χ2 = 28.51, p < 0.001). Furthermore, the high-risk group showed a higher minimum (absolute value) of trunk angular velocity along the mediolateral axis compared to the low-risk group (χ2 = 9.80, p = 0.007). The maximum trunk angular velocity along the vertical axis (r = 0.66, p < 0.001) and the minimum trunk angular velocity along the mediolateral axis (r = 0.51, p = 0.003) were significantly correlated with the BBS score. We found that post-stroke patients with a high risk of falling exhibited slower trunk rotation angular velocity and faster trunk flexion angular velocity during turning compared to low-risk groups. Our findings suggest that despite the decrease during turning speed due to poor balance control, post-stroke patients with a high risk of falling exhibit a greater disturbance in the sagittal plane.